Development of a Sleep Assessment Module in the Automated Self-Administered 24-Hour (ASA24) Dietary Assessment Tool: New Research Opportunities. (7th June 2021) - Shams-White, Marissa; O'Connor, Lauren; O'Connor, Sydney; Miller, Amy; Mittl, Beth; Nicholson, Tom; Kaefer, Christie; Herrick, Kirsten
Abstract: Objectives: To develop a sleep assessment module in ASA24 to capture self-reported sleep behavior as an optional enhancement to the ASA24 Dietary Assessment Tool for adults. Methods: Multiple self-reported sleep assessment tools were considered in module development, including the National Sleep Foundation Sleep Diary, the Activities Completed over Time in 24-hours (ACT24), Munich Chronotype Questionnaire (MCTQ), and the Consensus Sleep Diary (CSD) Core. Priority was given to minimal need for adaptation, questionnaire length to reduce survey fatigue, incorporating plain language, and optimizing for implementation in 24 hour recalls (24HR) and food records. Researchers with expertise in meal timing and sleep were consulted for feedback on content and utility and programmers with expertise in survey design were consulted on implementation. Lastly, the online data collection process and ASA24 System's output data files were tested for accuracy. Results: The ASA24 sleep module contains ten questions and can be administered immediately following dietary assessment. Eight CSD Core questions were adapted to assess time in bed, time trying to go to sleep, and length of time to fall asleep; number and duration of nocturnal awakenings; wake time and time out of bed for the day; and perceived sleep quality. Two questions were added to capture sleep quality and comparability of reported sleep to a usual night's sleep. For users completing a 24HR, the module includes two questions on time of awakening and sleep quality immediately preceding the first reported meal; all 10 sleep questions are asked for the sleep period immediately following the last meal (i.e., 12 questions total), allowing for assessment of the impact of diet on sleep. In contrast, a food record is completed on the same day users consume the food, and thus all sleep questions address the sleep window prior to the first meal; a single record can be used to assess the impact of sleep on diet. Consecutive days of records can also be collected to capture sleep pre- and post-eating windows. Conclusions: The ASA24 sleep module can assess sleep timing and quality and will be available in Fall 2021. Researchers can soon leverage this novel resource to examine the association of sleep with timing of eating and other chrononutrition variables. Funding Sources: This project has been funded by the NIH.